Airborne Observations of Reactive Inorganic Chlorine and Bromine Species in the Exhaust of Coal‐Fired Power Plants. Issue 19 (2nd October 2018) - Lee, Ben H.; Lopez‐Hilfiker, Felipe D.; Schroder, Jason C.; Campuzano‐Jost, Pedro; Jimenez, Jose L.; McDuffie, Erin E.; Fibiger, Dorothy L.; Veres, Patrick R.; Brown, Steven S.; Campos, Teresa L.; Weinheimer, Andrew J.; Flocke, Frank F.; et al.
Abstract: We present airborne observations of gaseous reactive halogen species (HCl, Cl2, ClNO2, Br2, BrNO2, and BrCl), sulfur dioxide (SO2 ), and nonrefractory fine particulate chloride (pCl) and sulfate (pSO4 ) in power plant exhaust. Measurements were conducted during the Wintertime INvestigation of Transport, Emissions, and Reactivity campaign in February–March of 2015 aboard the NCAR‐NSF C‐130 aircraft. Fifty air mass encounters were identified in which SO2 levels were elevated ~5 ppb above ambient background levels and in proximity to operational power plants. Each encounter was attributed to one or more potential emission sources using a simple wind trajectory analysis. In case studies, we compare measured emission ratios to those reported in the 2011 National Emissions Inventory and present evidence of the conversion of HCl emitted from power plants to ClNO2 . Taking into account possible chemical conversion downwind, there was general agreement between the observed and reported HCl:SO2 emission ratios. Reactive bromine species (Br2, BrNO2, and/or BrCl) were detected in the exhaust of some coal‐fired power plants, likely related to the absence of wet flue gas desulfurization emission control technology. Levels of bromine species enhanced in some encounters exceeded those expected assuming all of the native bromide in coal was released to the atmosphere, though there was no reported use of bromide salts (as a way to reduce mercury emissions) during Wintertime INvestigation of Transport, Emissions, and Reactivity observations. These measurements represent the first ever in‐flight observations of reactive gaseous chlorine and bromine containing compounds present in coal‐fired power plant exhaust. Key Points: Gaseous inorganic chlorine and bromine species were observed in the exhaust of coal‐fired power plants during the WINTER flight campaign We present evidence of the conversion of hydrogen chloride (HCl) emitted from power plants to nitryl chloride (ClNO2 ) downwind of a source Observed levels of Br2, BrNO2, and BrCl in some plumes strongly suggest artificial enhancement of bromide in the coal